E.P. Thompson and cultural sociology: questions of poetics, capitalism and the commons - Stevenson, Nick (SAGE, 2017)
There is currently a need for cultural sociology to readdress the work of humanistic and cultural Marxism. While more recently much of this work has been dismissed the appearance of more radical social movements and the on-going crisis of neoliberalism suggests that it still has much to tell us. In this respect, this article seeks to readdress the writing of historian E.P.Thompson arguing that his work on the class based and other social movements, poetics, critique of positivism and economic reason, utopia and work on the idea of the commons all has much to offer more contemporary scholarship. While the article recognises that the cultural Marxism of figures like Thompson can-not simply be resurrected it does continue to offer a number of critical insights lacking from other traditions within cultural sociology. By readdressing the internal complexity of Thompson’s writing the argumentative strategy of this article suggests that cultural sociology needs to move beyond more simplistic understandings of cultural Marxism and more carefully explore what it has to offer.